Inferior vena cava injury above the renal veins - Porras, Yamandú; Chavarría, Tabaré (Cirugía del Uruguay, 1976)
The authors present a case of wound of the inferior vena cava above the renal veins which was successfully solved by suture. It is remarked the urgency of the. procedure in order to stop the hemorrhage and the necessity of massive and immediate replenishment of volemia with fresh b!ood through the brachial venous system.